پا کستان میں اسلامی تہذیب سے متعلق تصنیفی و تحقیقی کام:نمایاں رجحانات کا مطالعہAuthorship and Research work on Islamic Civilization in Pakistan: A Study of Notable Trends (Al-Qamar, 2021)
This paper studies the notable trends in Compilation of literature on Islamic Civilization in Pakistan. In this study, fifty books written on different languages ​​on Islamic civilization were selected and analyzed From all this research, four trends of scholarly work on Islamic civilization came to light (introductory, historical, comparative, impactful). The study also introduces readers to previous work on Islamic civilization. The current research article is written in the context of the studies which are available in Arabic, English and Urdu languages, keeping in mind the importance of such trends and need of their analysis in evolution of respective area of study. The article comprises of three parts. In first part, the subject of research is introduced and importance of background of the work is elaborated. The second part includes a comparative evaluation of the scholarly work done in Arabic, English and Urdu languages. The conclusion is drawn and some consequent suggestions are proposed in third part of the article.
Keywords: Islamic civilization; literature; Pakistan; trends